PENGGUNAAN KATA SIFATけいようし[ I ] DAN KATA SIFAT けいようし[NA] DALAM KALIMAT BAHASA JEPANGPENGGUNAAN KATA SIFATけいようし[ I ] DAN KATA SIFAT けいようし[NA] DALAM KALIMAT BAHASA JEPANG (THE USE OF ADJECTIVES けいようし[I] AND ADJECTIVES けいようし[NA] IN JAPANESE SENTENCES) - Ilke Janemralina Moniung (Kadera Bahasa, 2016)
Japanese adjective（けいようし) is different with Indonesian adjective. Japanese adjective（けいようし）categorized into two kinds, adjective (けいようし） -i and -na ending. The Japanese -i ending should follow adjectives with the last letters at -ii, -ai, -oi and -ui. Therefore, these adjectives（けいようし） are knownas -i for example: oishii おいしい –delicious, chiisai ちいさい –small, omoshiroi おもしろい – interesting, warui わるい –ugly. Japanese adjective（けいようし） meaning keiyoushi serves to show the state, characteristic or feeling which has -i ending. The method used in this research was descriptive. It is a precise method to achieve a maximal achievement of the research -i . Based on the analysis, a conclusion can be drawn regard to the usage of sentence pattern of keiyoushi -i ending adjective, they are: 1. The usage of -i ending adjective is to explain a condition state of a thing. 2. The less understanding in -i ending adjective usage pattern and the various kinds of new adjective, unknown meaning or unlearn clearly and detail. Those adjective are misunderstood as well as less practice in Japanese sentence examples. It is hoped to read more Japanese sentence that used -i ending adjective, increase self motivation by learn precisely and correctly, searching related reference that connect to the -i ending adjective.